Agricultural Cargo Transportation Logistics System Development - Napkhonenko, N; Zagirniak, D; Karaeva, M (International Journal of Engineering and Technology, 2018)
The urgency of transportation organization improvement in the system of agricultural products delivery to the countryâ€™s population under conditions of import substitution is substantiated here. The article proposes to use the logistic approach. The advantage of the approach is that it combines and considers the processes of harvesting, transportation and distribution of goods in reciprocal relationship; and on this basis the concept of united harvesting, transportation and distribution complex (HTS) is introduced. The main organizational schemes for agricultural products delivery from the producer to the places of consumption are considered. Mathematical formulation of the vegetables transportation system optimization at HTS complex is performed based on the inclusion of receiving and classification units (RCU) in the logistics chains of delivery from the producer to the places of agricultural products consumption. An optimized multi-factor economic and mathematical model is proposed. It allows to identify RCU rational locations and their capacity, to calculate the number of road transport vehicles necessary to deliver vegetable cargo in full, provided that the recipients are optimally assigned to the product suppliers and available vehicles are optimally distributed for all modes of transport. Methods of the process main characteristics calculation are described.Â Â